Principles and practice of lipidomics. Issue 1 (20th November 2014) - Vaz, Frédéric M.; Pras‐Raves, Mia; Bootsma, Albert H.; van Kampen, Antoine H. C.
Abstract: The technical advances in mass spectrometry, particularly the development of (ultra)‐high‐resolution/mass accuracy measurement capabilities in combination with refinement of soft ionization techniques, have increased the application and success of lipidomics to answer biological questions in relation to lipid metabolism. Together with other omics technologies, lipidomics has become an important tool to practice systems biology as lipids comprise a very significant part of the metabolome and play pleiotropic roles in cellular functions. As an increasing number of disorders are linked to lipid metabolism, lipidomics is used to search for biomarkers, understand disease mechanism and follow the efficacy of therapeutic options. This review provides a first introduction to the major methodological strategies currently used for mass spectrometry‐based lipidomics and associated data pre‐processing and analysis.